Another "Great Tolbachik" Eruption?. (21st May 2013) - Edwards, Ben; Belousov, Alexander; Belousova, Marina; Volynets, Anna; Melnikov, Dmitry; Chirkov, Sergey; Senyukov, Sergey; Gordeev, Evgenii; Muraviev, Yaroslav; Izbekov, Pavel; Demianchuk, Yury
Abstract: On 27 November 2012 at 1715 local time, a focused swarm of earthquakes was interpreted as the start of a new ongoing eruption on the south flank (Tolbachinsky Dol) of Plosky Tolbachik volcano in east central Kamchatka, Russia (Figure 1a) [Samoylenko et al., 2012]. Visual observations on 29 November showed ash shooting from two fractures as well as long, rapidly moving lava flows. Although the initial ash clouds reached 6 kilometers in height, subsequent ashfall has been limited to the area around the main vents, and no permanent settlements are in danger from advancing lava flows (the closest settlements are about 40 kilometers from the volcano). Including this eruption, six different volcanoes are presently active in Kamchatka.